36.8k views
3 votes
Find the quotient using polynomial long division:

1. (50y^3+10y^2-35y-7)divided by(5y-4)

2. (8m^4-4m^2+m+4)divided by(2m+1)

1 Answer

5 votes

(1)
50y^3=5y\cdot 10y^2, and


10y^2\cdot(5y-4)=50y^3-40y^2

Subtract this from
50y^3+10y^2-35y-7 to get a remainder of


(50y^3+10y^2-35y-7)-(50y^3-40y^2)=50y^2-35y-7

What we've done here is show that


(50y^3+10y^2-35y-7)/(5y-4)=10y^2+(50y^2-35y-7)/(5y-4)

We can keep going as long as the degree of the remainder's numerator is at least the same as the degree of its denominator.

Next,
50y^2=5y\cdot 10y, and


10y\cdot(5y-4)=50y^2-40y

Subtract this from the previous remainder to get a new remainder of


(50y^2-35y-7)-(50y^2-40y)=5y-7

which means


(50y^3+10y^2-35y-7)/(5y-4)=10y^2+10y+(5y-7)/(5y-4)

Finally,
5y=5y\cdot1, and


1\cdot(5y-4)=5y-4

Subtract this from the previous remainder to get


(5y-7)-(5y-4)=-3

So we end up with


(50y^3+10y^2-35y-7)/(5y-4)=\boxed{10y^2+10y+1}-\frac3{5y-4}

(the quotient is the expression in the box)

(2) Using the same process as before:


8m^4=2m\cdot4m^3


4m^3\cdot(2m+1)=8m^4+4m^3


(8m^4-4m^2+m+4)-(8m^4+4m^3)=-4m^3-4m^2+m+4


\implies(8m^4-4m^2+m+4)/(2m+1)=4m^3-(4m^3+4m^2+m+4)/(2m+1)


-4m^3=2m\cdot(-2m^2)


-2m^2\cdot(2m+1)=-4m^3-2m^2


(-4m^3-4m^2+m+4)-(-4m^3-2m^2)=-2m^2+m+4


\implies(8m^4-4m^2+m+4)/(2m+1)=4m^3-2m^2-(2m^2-m-4)/(2m+1)


-2m^2=2m\cdot(-m)


-m\cdot(2m+1)=-2m^2-m


(-2m^2+m+4)-(-2m^2-m)=2m+4


\implies(8m^4-4m^2+m+4)/(2m+1)=4m^3-2m^2-m+(2m+4)/(2m+1)


2m=2m\cdot1


1\cdot(2m+1)=2m+1


(2m+4)-(2m+1)=3


\implies(8m^4-4m^2+m+4)/(2m+1)=\boxed{4m^3-2m^2-m+1}+\frac3{2m+1}

User Proseosoc
by
5.4k points